EPIDEMIOLOGY AND CLINICAL CHARACTERISTICS OF MUMPS AMONG CHILDREN AND ADOLESCENTS: A CROSS-SECTIONAL STUDY IN CISOKA PUSKESMAS, INDONESIA - Muhammad Ikmal Syafi'i; David Christian; Indri; Trisna Amerdista (International Journal of Nursing and Midwifery Science (IJNMS), 2025)
Background: Mumps remains a vaccine-preventable illness with periodicoutbreaks in areas with low immunization coverage. Rural settings oftenshow higher susceptibility due to limited healthcare access.Aims: To determine the prevalence and clinical characteristics of mumpsamong children and adolescents at Cisoka Puskesmas, Indonesia.Methods: A cross-sectional study was conducted on all pediatric patientsclinically diagnosed with mumps from January to March 2025 based onWHO criteria. Demographic data, MR vaccination status, clinical features,and household exposures were obtained through interviews and clinicalevaluation. Descriptive analysis was performed using SPSS 26.0.Result: Seventy-six mumps cases were identified, yielding a prevalence of4.38%. The highest age-specific prevalence occurred in children aged 6–11years (6.45%). Unilateral parotitis accounted for 71.1% of cases. Commonsymptoms included fever (96.1%), chewing pain (61.8%), and painfulswallowing (51.3%). Only 59.2% had received MR vaccination, and 65.8%lived in close contact with at least one active smoker.Conclusion: Mumps continues to circulate among the pediatric population inrural Tangerang, driven by inadequate MR vaccination coverage andmodifiable household-level exposures such as close contact with smokers.Strengthening immunization uptake and reducing preventable exposures arecritical to mitigate future outbreaks.